Macrophage Plasticity in Reproduction and Environmental Influences on Their Function - Chambers, Megan; Rees, April; Cronin, James G.; Nair, Manju; Jones, Nicholas; Thornton, Catherine A. (Frontiers in Immunology, 2021)
Macrophages are key components of the innate immune system and exhibit extensive plasticity and heterogeneity. They play a significant role in the non-pregnant cycling uterus and throughout gestation they contribute to various processes underpinning reproductive success including implantation, placentation and parturition. Macrophages are also present in breast milk and impart immunomodulatory benefits to the infant. For a healthy pregnancy, the maternal immune system must adapt to prevent fetal rejection and support development of the semi-allogenic fetus without compromising host defense. These functions are dependent on macrophage polarization which is governed by the local tissue microenvironmental milieu. Disruption of this microenvironment, possibly by environmental factors of infectious and non-infectious origin, can affect macrophage phenotype and function and is linked to adverse obstetric outcomes, e.g. spontaneous miscarriage and preterm birth. Determining environmental influences on cellular and molecular mechanisms that control macrophage polarization at the maternal-fetal interface and the role of this in pregnancy complications could support approaches to alleviating adverse pregnancy outcomes.